RELASI ANTAR AKTOR DALAM KOMPETISI LAYANG-LAYANG DI DENPASAR JELANG PEMILU LEGISLATIF TAHUN 2014 - wigraheni, Wina wigraheni; Erviantono, Tedi; S.Fil.,MA, Bandiyah (Jurnal Nawala Politika, 2015)
ABSTRACT In general, the race kite competed in a simple, unlike the case with Denpasar Bali kite into an arts and culture into public appeal. See enthusiastic people who are very high and increasing number of participants race each year, it indicates that the race kite got a great welcome from the public. The existence of race kite began ogled by the actors, especially the legislative candidates who run for the legislative  elections  in 2014.  The  objective  is to get  the  support  of the  voice  of sekaa  kites.  The purpose  of  this  study  was  to  determine  how  the  actors  in  relation  to  compete  in  a  race  kite  in Denpasar ahead of legislative elections in 2014. In order to obtain an answer from the formulation of the problem is done with descriptive  qualitative  methods, such as by interviews  with key informants, observations in the field, and documentation. Results  from  this study  can be concluded  is first,  ahead  of the  legislative  elections  many candidates became involved in providing assistance,  in the form of materials such as funding for the cost of making kites is done in their own hamlets or villages. The provision of such assistance lead to a reciprocal relationship  between candidates with sekaa kites, and equally mutual benefit. Secondly, before the 2014 legislative elections individual candidates sekaa more aggressively approached them with participating  enliven kite kite race in row to get closer to their constituents  and keep the noise down so as not to split. Sekaa  organization  and kites into the vehicle  and the political  machine  in gaining  a voice  in the legislative  elections  of 2014,  this phenomenon  was common  in those  days before  the  election,  but  it  is  interesting  because  it  dihimpuni  by sekaa  organizations  that  do  not necessarily exist elsewhere.   Keywords: Pelangi Bali, Kites Team, Candidates, Legislative Elections